Product awareness and learning motivation on plantae topics through project-based learning with halal literacy - Firdaus, Muhammad Taufiq; Wulandari, Ismi Ayu; Windayani, Neneng; Supriadin, Asep (STKIP Persada Khatulistiwa Sintang, 2024)
In the ever-evolving world of education, an in-depth understanding of the learning process is essential. Lecture methods that tend to be monotonous often reduce students' motivation to learn, which in turn has an impact on decreasing learning outcomes, especially in plant material. Project-based learning has emerged as an alternative to increase students' interest in learning. This study aims to instill halal literacy awareness while influencing interest in purchasing halal products through a project-based learning approach on plantae material. A quantitative approach with a targeted survey design was used in this study. Thus, we used the purposive sampling technique to define 28 students as respondents. Data were collected through a questionnaire with a Likert scale (1-4). The analysis results show that the student awareness variable (X1) has a negative correlation with halal literacy project-based learning. Through multiple linear regression analysis, no symptoms of multicollinearity or heteroscedasticity were found. Halal literacy project-based learning contributed 30.8% to increasing students' awareness and interest in purchasing halal products. Thus, project-based learning is proven effective in increasing students' interest in learning, especially in plantae material.